Antioxidant-grafted modified high-voltage direct-current cable polyethylene material and preparation method thereof

By grafting the antioxidant GS onto the polyethylene molecular chain, the problems of space charge accumulation and easy migration of antioxidant in the insulating material of high-voltage DC cables are solved, and the material compatibility and long-term stability are achieved, and the service life of the cable is extended.

CN119859220APending Publication Date: 2025-04-22BEIJING SMART ENERGY RES INST +1

Patent Information

Application Number
CN202510120008.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-25
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the problem of space charge accumulation in high-voltage DC cable insulating materials, and antioxidants are prone to move out, poor compatibility, which affects the long-term stability and performance of the material.

Method used

By grafting the antioxidant GS with polyethylene, the antioxidant GS is grafted onto the polyethylene molecular chain by free radical addition reaction, thereby improving the compatibility and stability of the antioxidant.

Benefits of technology

The good dispersion and migration resistance of antioxidants are achieved, the space charge characteristics of polyethylene insulating materials are significantly improved, the service life of the cable is extended, and the overall performance of the material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859220A_ABST
    Figure CN119859220A_ABST
Patent Text Reader

Abstract

The invention discloses an antioxidant grafted modified high-voltage direct-current cable polyethylene material and a preparation method thereof, and belongs to the technical field of modification of high-voltage direct-current cable insulating materials. The material is prepared from the following raw materials: polyethylene, an antioxidant GS and an initiator DCP. The preparation method comprises the following steps: firstly, mixing the polyethylene, the antioxidant GS and the initiator DCP to obtain an antioxidant GS / initiator DCP / polyethylene material blend; and then carrying out grafting and cross-linking treatment on the blend to obtain the cross-linked polyethylene insulating material grafted and modified by the antioxidant. The antioxidant grafted polyethylene material prepared by the invention has excellent oxidation resistance, electrical properties and good color, and is beneficial to prolonging the service life of a high-voltage direct-current cable. The antioxidant is grafted to a polyethylene molecular chain, so that the emigration of the antioxidant can be reduced, the compatibility of the antioxidant and a polyethylene matrix is improved, the oxidation resistance of polyethylene is improved, and the accumulation of space charges of a polyethylene insulating material can be inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-voltage direct current cable insulation material modification, and in particular to an antioxidant-grafted modified high-voltage direct current cable polyethylene material and a preparation method thereof. Background Art

[0002] Low-density polyethylene (LDPE) has the characteristics of high insulation resistance, good pressure resistance, low dielectric loss, easy processing, and low cost. It is widely used in cable insulation materials. Under high-voltage DC electric fields, the problem of space charge accumulation in insulating materials has become the main factor restricting the development of high-voltage DC cables. Space charge will cause the local electric field of the insulating material to be distorted, making the electric field of the insulating layer uneven, which will not only accelerate the aging of the insulating material, but even cause insulation breakdown, thereby shortening the service life of the cable. By grafting and modifying polyethylene with polar molecules and introducing deep traps, the injection of charges of the same polarity can be reduced, and the space charge characteristics can be significantly improved.

[0003] LDPE is prone to aging under heat, oxygen and other conditions during storage, processing and use, resulting in a decrease in its physical and chemical properties, mechanical properties and electrical properties, which in turn reduces the stability of cable operation and reduces the service life of the cable. In practical applications, adding antioxidants is the most convenient and effective way to delay the aging of LDPE. However, most antioxidants are small molecular weight compounds containing polar groups, which have poor compatibility with the non-polar LDPE matrix and are easily migrated, extracted and volatilized from LDPE, thus affecting the protective effect of the antioxidant. The migrated antioxidants will also cause pollution to the surrounding environment. Among polyethylene cable materials, the most commonly used antioxidant is AO300 [4,4′-thiobis(2-tert-butyl-5-methylphenol)]. Through molecular dynamics simulation calculations ( Figure 1 The dissolution parameter is 18.4 (J / cm 3 ) 1 / 2 , and LDPE (solubility parameter is 16.3 (J / cm 3 ) 1 / 2 ) phase difference is relatively large, making it difficult to evenly disperse in the polyethylene matrix. In addition, antioxidant AO300 not only affects the peroxide (such as DCP, diisopropylbenzene peroxide) / polyethylene cross-linking reaction (reducing the degree of cross-linking of polyethylene), but also affects the color of polyethylene. During the crystallization process of LDPE, the antioxidant is discharged from the ordered crystalline region and gathered in the amorphous region, becoming an important source of charge in the LDPE insulation material, thereby further affecting other electrical properties of the cable insulation material.

[0004] In the prior art, although the antioxidant grafting modification polyethylene method delays the aging of LDPE to a certain extent, it is still insufficient in solving the problem of space charge accumulation. For example, the antioxidant used in patent CN111393785B, such as 2-(2-hydroxy-3-tert-butyl-5-methylbenzyl)-4-methyl-6-tert-butylphenyl acrylate (antioxidant GM), has a solubility parameter (17.8 (J / cm 3 ) 1 / 2 ) and LDPE (solubility parameter is 16.3 (J / cm 3 ) 1 / 2 ) is quite different, resulting in poor dispersibility in LDPE. In addition, the OH bond dissociation energy of antioxidant GM is relatively high (367.9 kJ / mol), while the CH bond dissociation energy of LDPE is relatively low (436.3 kJ / mol), which limits the antioxidant effect and stability of the antioxidant. In addition, the mobility of antioxidant GM is relatively high, and it is easy to fall off from the polyethylene matrix, resulting in a weakening of its protective effect.

[0005] The existing antioxidant grafting modification method for polyethylene has not yet effectively solved the problem of space charge accumulation in polyethylene under high-voltage DC electric fields. Due to the low polarity of the polyethylene matrix, the traditional grafting modification method is difficult to effectively inhibit the accumulation of space charge, and the migration and volatilization problems of antioxidants have not been completely solved, resulting in limited long-term stability and performance in cable applications. Summary of the invention

[0006] The present invention aims at the problems of space charge accumulation and easy migration of antioxidants in high-voltage DC cable insulation materials in the prior art, and provides an antioxidant-grafted modified high-voltage DC cable polyethylene material and a preparation method thereof, in order to obtain a high-voltage DC cable insulation material with excellent electrical properties and anti-aging properties.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] The first aspect of the present invention provides an antioxidant grafted modified high-voltage DC cable polyethylene material, wherein the raw materials for its preparation include, by mass, 100 parts of polyethylene, 0.1 to 5 parts of initiator DCP (diisopropylbenzene peroxide), and 0.05 to 3 parts of antioxidant GS (2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate).

[0009] Furthermore, the molecular weight of the polyethylene is a weight average molecular weight of 60,000-120,000.

[0010] Furthermore, the polyethylene is low-density polyethylene (LDPE).

[0011] The solubility parameter of the antioxidant GS selected in the present invention is (15.6 (J / cm 3 ) 1 / 2 ) is closer to LDPE, and the OH bond dissociation energy (360.2 kJ / mol) is also lower (e.g. Figure 1 As shown), it can be inferred that the antioxidant GS has good compatibility (dispersibility) and better protective effect.

[0012] The second aspect of the present invention provides a method for preparing the above-mentioned antioxidant grafted modified high-voltage DC cable polyethylene material, comprising the following steps:

[0013] (1) mixing polyethylene, antioxidant GS, and initiator DCP and kneading them to obtain an antioxidant / initiator / polyethylene blend;

[0014] (2) hot pressing the antioxidant / initiator / polyethylene blend in a flat vulcanizer to obtain a hot pressing sample;

[0015] (3) The hot pressed sample is subjected to grafting and cross-linking treatment to obtain an antioxidant grafted modified high voltage DC cable polyethylene material.

[0016] Furthermore, the mixing temperature in step (1) is 100 to 130° C., and the mixing time is 2 to 6 minutes.

[0017] Furthermore, the mixing process in step (1) includes: melting the polyethylene, adding the antioxidant GS and mixing for 1 to 3 minutes, and then adding the initiator DCP and mixing for 1 to 3 minutes.

[0018] Furthermore, the temperature of the hot pressing molding is 110-140° C., the pressure is 10-20 MPa, and the time is 20-40 min.

[0019] Furthermore, the grafting and cross-linking treatment temperature is 160-200° C., the pressure is 10-20 MPa, and the time is 20-50 min.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention provides an antioxidant grafted modified high-voltage DC cable polyethylene material and a preparation method thereof. The antioxidant GS is grafted onto the polyethylene molecular chain through a free radical addition reaction, thereby solving the problems of easy migration of the antioxidant and poor compatibility with the polyethylene matrix in the prior art. Compared with the traditional antioxidants AO300 and GM, the antioxidant GS grafted modified material exhibits excellent comprehensive properties, including a longer oxidation induction period, higher breakdown strength and more stable color. At the same time, the grafting of the antioxidant GS significantly improves the spatial charge characteristics of the polyethylene insulating material, reduces the occurrence of electric field distortion, and effectively improves the application performance of the material in the high-voltage DC cable. The material of the present invention not only has excellent anti-aging performance, but also has good anti-migration properties, thereby extending the service life of the high-voltage DC cable. In addition, the method of the present invention is simple and easy to operate, and has a low production cost, which provides reliable technical support and economic benefits for the industrial application of high-voltage DC cable insulating materials, and has significant promotion value. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 (a) Solubility parameters and C-H bond dissociation energy of polyethylene PE obtained by molecular simulation; (b) Solubility parameters and OH bond dissociation energy of antioxidant AO300 obtained by molecular simulation; (c) Solubility parameters and OH bond dissociation energy of antioxidant GS obtained by molecular simulation; (d) Solubility parameters and OH bond dissociation energy of antioxidant GM obtained by molecular simulation.

[0023] Figure 2 This is the color of the samples after mixing DCP / PE, antioxidant GM / DCP / PE, antioxidant AO300 / DCP / PE, and antioxidant GS / DCP / PE.

[0024] Figure 3 These are samples of GS / DCP / PE and AO300 / DCP / PE after hot pressing.

[0025] Figure 4 These are the space charge curves of AO300 / DCP / PE, GM / DCP / PE, and GS / DCP / PE hot-pressed samples. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. It is worth noting that the methods used in the present invention are conventional methods unless otherwise specified; the raw materials and devices used are conventional commercially available products unless otherwise specified, and their sources are not specifically limited.

[0027] The oxidation induction period test process of the present invention is as follows: according to GB / T 19466.6-2009, 15 mg of sample is placed in an aluminum dish and heated at N 2 The temperature was raised to 180°C at a rate of 20°C / min under protection, and then switched to O 2 Until the test is completed, the gas flow rate is 50 ml / min.

[0028] Example 1

[0029] (1) Weigh 40 g of LDPE and melt it in a torque rheometer at 110°C and 40 r / min, then add 0.12 g of antioxidant GS and mix for 2 min, and finally add 0.8 g of initiator DCP and mix for 2 min to obtain an antioxidant / initiator / polyethylene blend. The color of the sample after mixing is as follows: Figure 2 As shown in the figure, it can be seen that the sample is white, and the addition of antioxidants does not affect the color of the sample;

[0030] (2) hot pressing the antioxidant / initiator / polyethylene blend in step (1) for 20 minutes at 120° C. and 15 MPa using a flat-plate vulcanizer to obtain a hot-pressed sample;

[0031] (3) The hot pressing sample in step (2) is heated to 180° C., and hot pressing is continued at 15 MPa for 20 min. After cooling, an antioxidant-grafted modified high-voltage DC cable polyethylene material is obtained.

[0032] The samples after hot pressing are as follows Figure 3 As shown in the figure, it can be seen that the sample is transparent and uniform, and the antioxidant can be evenly dispersed in the resin matrix.

[0033] The material was subjected to aging and electrical performance tests. The oxidation induction period of the material was 7.5 min and the crosslinking density was 10.72×10 -4 mol / mL, the breakdown strength is 402kV / mm, and the space charge curve of the material is as follows Figure 4 shown.

[0034] Example 2

[0035] (1) 40 g of LDPE was weighed and melted in a torque rheometer at 110° C. and 40 r / min, and then 0.2 g of antioxidant GS was added and mixed for 2 min. Finally, 0.8 g of initiator DCP was added and mixed for 2 min to obtain an antioxidant / initiator / polyethylene blend;

[0036] (2) hot pressing the antioxidant / initiator / polyethylene blend in step (1) for 20 minutes at 120° C. and 15 MPa using a flat-plate vulcanizer to obtain a hot-pressed sample;

[0037] (3) The hot pressing sample in step (2) is heated to 180° C., and hot pressing is continued at 15 MPa for 20 min. After cooling, an antioxidant-grafted modified high-voltage DC cable polyethylene material is obtained.

[0038] The material was subjected to aging and electrical property tests. The oxidation induction period of the material was 10.3 min and the crosslinking density was 11.13 × 10 -4 mol / mL, and the breakdown strength is 398kV / mm.

[0039] Example 3

[0040] (1) 40 g of LDPE was weighed and melted in a torque rheometer at 110° C. and 40 r / min, and then 0.4 g of antioxidant GS was added and mixed for 2 min. Finally, 0.8 g of initiator DCP was added and mixed for 2 min to obtain an antioxidant / initiator / polyethylene blend;

[0041] (2) hot pressing the antioxidant / initiator / polyethylene blend in step (1) for 20 minutes at 120° C. and 15 MPa using a flat-plate vulcanizer to obtain a hot-pressed sample;

[0042] (3) The hot pressing sample in step (2) is heated to 180° C., and hot pressing is continued at 15 MPa for 20 min. After cooling, an antioxidant-grafted modified high-voltage DC cable polyethylene material is obtained.

[0043] The material was subjected to aging and electrical performance tests. The oxidation induction period of the material was 13.2 min and the crosslinking density was 10.16×10 -4 mol / mL, and the breakdown strength is 390kV / mm.

[0044] In order to illustrate the effect of the present invention, no antioxidant, antioxidant AO300, and reactive antioxidant 2-(2-hydroxy-3-tert-butyl-5-methylbenzyl)-4-methyl-6-tert-butylphenyl acrylate (antioxidant GM, the antioxidant selected by patent CN 111393785 B) are selected as comparative examples. The comparative examples are provided as follows:

[0045] Comparative Example 1

[0046] The difference from Example 1 is that no antioxidant is added in step (1), and the other steps are the same as Example 1.

[0047] After testing, the oxidation induction period of the material is 2.6min and the crosslinking density is 10.23×10 -4 mol / mL, and the breakdown strength is 391kV / mm.

[0048] Comparative Example 2

[0049] The difference from Example 1 is that in step (1), 0.12 g of antioxidant GS is replaced with 0.08 g of antioxidant AO300. At this time, the antioxidant AO300 and the antioxidant GS are equimolar. The other steps are the same as Example 1.

[0050] Figure 2 It can be observed that the AO300 / DCP / PE mixture appears red after mixing.

[0051] Figure 3 It can be observed that the AO300 dispersion is uneven in the AO300 / DCP / PE sample after hot pressing.

[0052] After testing, the oxidation induction period of the material was 12.5min and the crosslinking density was 9.97×10 -4 mol / mL, and the breakdown strength is 387kV / mm.

[0053] The space charge curve of AO300 / DCP / PE sample is as follows: Figure 4 shown.

[0054] Comparative Example 3

[0055] The difference from Example 1 is that in step (1), 0.12 g of antioxidant GS is replaced with 0.09 g of antioxidant GM. At this time, the antioxidant GS and the antioxidant GM are equimolar. The other steps are the same as Example 1.

[0056] Figure 2 It can be observed that the GM / DCP / PE mixture after mixing shows obvious yellowing.

[0057] After testing, the oxidation induction period of the material was 4.7 min and the crosslinking density was 10.83×10 -4 mol / mL, and the breakdown strength is 385kV / mm.

[0058] The space charge curve of GM / DCP / PE sample is as follows Figure 4 shown.

[0059] It can be seen from the above test examples that the comprehensive performance (oxidation induction period, breakdown strength, color) of the polyethylene insulation material modified by the grafting of the antioxidant GS of the present invention is better than that of the polyethylene insulation material modified by the grafting of the antioxidant GM. Compared with the free type AO300, GS has good dispersibility, good migration resistance, good color in the PE matrix, has no effect on the cross-linking degree of PE, and even has the effect of improving the cross-linking degree (within a certain GS content range). In addition, after the samples of Example 1 and Comparative Example 2 were subjected to solvent extraction treatment, the oxidation induction period of the samples was tested. The results showed that the oxidation induction period of the free antioxidant AO300 / DCP / PE was 3.5min, while the oxidation induction period of the grafted antioxidant GS / DCP / PE was 6.7min, indicating that the grafted antioxidant GS has good migration resistance. In addition, the spatial charge accumulation phenomenon of the GS / DCP / PE sample is not obvious ( Figure 4 As shown), it is better than GM / DCP / PE or AO300 / DCP / PE.

[0060] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.

Claims

1. An antioxidant-grafted modified high-voltage DC cable polyethylene material, the raw materials for its preparation include, by weight: 100 parts of polyethylene, 0.1 to 5 parts of initiator DCP (diisopropylbenzene peroxide), and 0.05 to 3 parts of antioxidant GS (2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate).

2. The antioxidant grafted modified high voltage DC cable polyethylene material according to claim 1, characterized in that: The weight average molecular weight of the polyethylene is 60,000-120,000.

3. The antioxidant grafted modified high voltage DC cable polyethylene material according to claim 1, characterized in that: The polyethylene is low-density polyethylene.

4. The method for preparing the antioxidant grafted modified high voltage DC cable polyethylene material according to any one of claims 1 to 3, comprising the following steps: (1) mixing polyethylene, antioxidant GS, and initiator DCP and kneading them to obtain an antioxidant / initiator / polyethylene blend; (2) hot pressing the antioxidant / initiator / polyethylene blend to obtain a hot pressing sample; (3) The hot pressed sample is subjected to grafting and cross-linking treatment to obtain an antioxidant grafted modified high voltage DC cable polyethylene material.

5. The preparation method according to claim 4, characterized in that: The mixing temperature in step (1) is 100-130° C., and the mixing time is 2-6 min.

6. The preparation method according to claim 5, characterized in that: The mixing process of step (1) comprises: melting polyethylene, adding antioxidant GS and mixing for 1 to 3 minutes, and then adding initiator DCP and mixing for 1 to 3 minutes.

7. The preparation method according to claim 4, characterized in that: The temperature of the hot pressing molding is 110-140° C., the pressure is 10-20 MPa, and the time is 20-40 min.

8. The preparation method according to claim 4, characterized in that: The temperature of the grafting and cross-linking treatment is 160-200° C., the pressure is 10-20 MPa, and the time is 20-50 minutes.

Citation Information

Patent Citations

  • An antioxidant-grafted cross-linked polyethylene insulation material for high-voltage DC cables and its preparation method

    CN111393785B

Cited By

  • Crosslinkable polyethylene insulation material and application thereof, crosslinked polyethylene insulation material and preparation method and application thereof

    CN121378977A

  • Cross-linkable polyethylene insulation material and its application, cross-linked polyethylene insulation material and its preparation method and application

    CN121378977B